2012
DOI: 10.1007/s11064-012-0724-2
|View full text |Cite
|
Sign up to set email alerts
|

Downregulating the Canonical Wnt/β-catenin Signaling Pathway Attenuates the Susceptibility to Autism-like Phenotypes by Decreasing Oxidative Stress

Abstract: Although a growing body of evidence supports the importance of the Wnt/β-catenin signaling pathway and oxidative stress in the pathogenesis of autism, it is unclear whether a relationship exists between the Wnt/β-catenin pathway and oxidative homeostasis. The present study examines the effects of sulindac, a small molecule inhibitor of the Wnt/β-catenin signaling pathway, on the oxidative status of rats that are prenatally exposed to valproic acid (VPA), which is used in an animal model of autism. Our data sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 49 publications
6
69
0
1
Order By: Relevance
“…A study observed decreased SOD and GSH-Px activity, as well as increased MDA content of the substantia nigra in PD rats, which was similar to our findings [32]. The activation of the Wnt/β-catenin signaling pathway results in imbalanced oxidative homeostasis as evidenced by the relationship between inhibited OS and over-activated Wnt/β-catenin signaling pathway in another study [33, 34]. In terms of the qRT-PCR and western blot assays, the results showed that in comparison with the sham or the control groups, mRNA and protein expression of GSK-3β increased, while GSK-3β-Ser9 protein expression and β-catenin and cyclinD1 mRNA and protein expression decreased in the other groups.…”
Section: Discussionsupporting
confidence: 90%
“…A study observed decreased SOD and GSH-Px activity, as well as increased MDA content of the substantia nigra in PD rats, which was similar to our findings [32]. The activation of the Wnt/β-catenin signaling pathway results in imbalanced oxidative homeostasis as evidenced by the relationship between inhibited OS and over-activated Wnt/β-catenin signaling pathway in another study [33, 34]. In terms of the qRT-PCR and western blot assays, the results showed that in comparison with the sham or the control groups, mRNA and protein expression of GSK-3β increased, while GSK-3β-Ser9 protein expression and β-catenin and cyclinD1 mRNA and protein expression decreased in the other groups.…”
Section: Discussionsupporting
confidence: 90%
“…In VPA exposure rats, the levels of WNT1 and WNT2 in the prefrontal cortex and hippocampus are up-regulated (Kalkman, 2012). Down-regulation of the Wnt signaling pathway attenuates the susceptibility to autism-like phenotypes in VPA-exposed mice (Zhang et al, 2012) (Zhang et al, 2015). Consistent with these reports, our study showed that Wnt signaling was over-activated in VPA-exposed rats, and inhibition of Wnt signaling by sulindac relieved ASD-like behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…The level of p-ERK was unchanged (n = 6, not significant versus control group). Recent research showed that canonical Wnt signaling is activated in VPA-exposed ASD rats (Zhang et al, 2012). Our study further validated this finding.…”
Section: Rapamycin Attenuates Vpa-induced Autophagy Suppression In Assupporting
confidence: 89%
See 1 more Smart Citation
“…The dysregulation of the Wnt pathway may contribute to the pathogenesis of neurodevelopmental disorders such as autism. Sundilac, an inhibitor of the Wnt/β-catenin pathway, decreased activated GSK3β levels and ameliorated repetitive/stereotypic activity as well as the learning, memory, and behavioral abnormalities of rat autism models [159]. Exposure to pyrithiamine, an anti-thiamine compound, also increases β-amyloid protein accumulation and GSK3 activity in the brain [160].…”
Section: Other Rolementioning
confidence: 99%